Iʿdād Mawād Taʿlīmīyah Tatakayyaf maʿa al-Jāʾiḥah: Wijhāt Naẓr min Muḥāḍirī al-Lughah al-ʿArabīyah fī Iḥdá al-Jāmiʿāt al-Islāmīyah al-Ḥukūmīyah bi-Indonesia - Mukroji Mukroji (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2021)
The Covid-19 epidemic has altered the entire educational system. Teachers must provide instruction and learning materials remotely using electronic learning mediums. This study aims to explore Arabic lecturers' perception of pandemic-sensitive learning material development using semi-structured online interviews with five Arabic language instructors at an Islamic University in Central Java, followed by email interviews. The findings showed two primary strategies for developing pandemic-adaptive materials, including harnessing one's creativity and resources and student collaboration. Additionally, the lecturers reported problems in developing teaching materials due to limited time and learning resources.